2020
DOI: 10.1002/rmv.2107
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses and pathogenesis of SARS‐CoV‐2 during an outbreak in Iran: Comparison with SARS and MERS

Abstract: SummaryThe beginning of 2020 has seen the emergence of COVID‐19, an outbreak caused by a novel coronavirus, SARS‐CoV‐2, an important pathogen for humans. There is an urgent need to better understand this new virus and to develop ways to control its spread. In Iran, the first case of the COVID‐19 was reported after spread from China and other countries. Fever, cough, and fatigue were the most common symptoms of this virus. In worldwide, the incubation period of COVID‐19 was 3 to 7 days and approximately 80% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
234
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 226 publications
(251 citation statements)
references
References 46 publications
5
234
0
12
Order By: Relevance
“…The typical innate immune response to SARS‐CoV‐2 is marked by suppressed type I interferon. TLR 7 plays an important role in the recognition of SARS‐CoV‐2 RNA and initiating the host innate immune response 58 . By increasing endosomal pH, HCQ reduces TLR 7 and TLR 9 affinity for viral RNA, thereby diminishing the induction of cytokines which may play a role in viral control including type I interferon, IL‐6, and IL‐12.…”
Section: Hcq and The Immune Systemmentioning
confidence: 99%
“…The typical innate immune response to SARS‐CoV‐2 is marked by suppressed type I interferon. TLR 7 plays an important role in the recognition of SARS‐CoV‐2 RNA and initiating the host innate immune response 58 . By increasing endosomal pH, HCQ reduces TLR 7 and TLR 9 affinity for viral RNA, thereby diminishing the induction of cytokines which may play a role in viral control including type I interferon, IL‐6, and IL‐12.…”
Section: Hcq and The Immune Systemmentioning
confidence: 99%
“…In consistent with our result, a previous study conducted by Liu, et al [3], documented NLR as the independent risk factor for prediction of severe illness in patients with SARS-CoV-2 infection which should rapidly hospitalized in ICU. So that, in 50% of patients with age ≥ 50 who had NLR ≥ 3.13 severe form of the disease were observed [3,10].…”
Section: Radiography Ndingsmentioning
confidence: 98%
“…These pathological damages might be attributable to indirect cytokines release syndrome (CRS) e.g. interleukin (IL)-1, IL-6 and TNF-α initiated by immune system and direct attack from SARS-CoV-2 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Critical state COVID-19 patients require the use of mechanical ventilation [5] and a study reported that about 9 to 11% of hospitalized patients, mainly elderly, required mechanical ventilation due to complications [6]. Severe conditions can lead to acute respiratory distress syndrome (ARDS) [7] with diffuse alveolar damage (DAD) characterized interstitial septal edema and hyaline membrane in the acute phase, as well as the proliferation of broblasts and septal brosis in the remodeling chronic phase [8].…”
Section: Introductionmentioning
confidence: 99%